Effect of periodic drying on energy utilization, product quality, and drying time - Baradey, Yehya; Hawlader, Mohammad Nurul Alam; Ismail, Ahmad Faris; Hrairi, Meftah (CRC Press - Taylor & Francis Group, 2017)
The quality and safety of food materials, especially those rich in nutritional value such as fruits and vegetables, have recently received great attention from researchers worldwide and have become the most significant research topic in industries. This can be attributed to the harmful effects likely to occur to human life due to consumption of spoilt food stuff (Rahman, 1999, p. 19). Approximately one third of global food production is wasted annually due to the lack of proper food preservation processes (Kumar et al., 2014). According to Karim and Hawlader (2005), about 30%–40% of total yearly production of fruits and vegetables in Bangladesh is lost due to improper food preservation processing. Baini and Langrish (2007) reported that between 40% and 45% of annual production of banana is lost due to mold growth and postharvest spoilage in India and Brazil. Dehydration technologies are considered the most widely used techniques for food preservation. The most common method in ancient times was solar drying. Nowadays, different types of drying are available for commercial use in the market place, such as freeze drying, osmotic dehydration, convective drying, and vacuum microwave drying. The most widely used dehydration